Peningkatan Kemandirian Lansia melalui Edukasi Pencegahan Demensia Berbasis Komunitas - Elis Noviati; Yuyun Rahayu; Ima Sukmawati; Rudi Kurniawan; Heni Marliany; Diny Nur Fauziyah; Nunung Aeni NM (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2026)
Introduction:Aging is a natural process characterized by a gradual decline in physical, cognitive, and functional abilities. One of the major health challenges among older adults is Demensia, which can significantly reduce independence and quality of life. Early prevention efforts through health education are essential to delay cognitive decline and maintain functional ability among the elderly. However, awareness and knowledge regarding dementia prevention among older adults and caregivers in community settings remain limited. Therefore, community service activities aimed at providing education on dementia prevention are important to support independent and healthy aging. Objective:The purpose of this community service program was to improve the independence of elderly participants at Daycare Lansia Setaman Aisyiah Ciamis through community-based education on dementia prevention conducted in April 2025. Methods:The methods used in this activity were participatory education consisting of lectures, interactive discussions, and simple cognitive stimulation exercises. Participants were provided with information regarding risk factors, early signs, and preventive strategies for Demensia, including healthy lifestyle practices, balanced nutrition, physical activity, and mental exercises. Pre-test and post-test evaluations were conducted to assess the improvement in participants’ knowledge and understanding. Result:The evaluation results indicated a significant increase in participants’ knowledge regarding dementia prevention, as shown by the improvement in post-test scores compared to pre-test results. Additionally, participants demonstrated better understanding and ability to apply simple cognitive and physical exercises that support independence. These findings suggest that the educational intervention effectively enhanced awareness and skills related to dementia prevention among the elderly. Conclusion:This community service activity was successfully implemented in April 2025 at Daycare Lansia Setaman Aisyiah Ciamis and resulted in improved knowledge and independence among elderly participants. The program contributes to promoting healthy aging and supports the development of community-based